Quirky to Cannes the works and production practices of director Marius Talampas - Valdez, Lorraine Shekinah C.; Venzon, Shaira Kristine M. (Quezon City University of the Philippines, Diliman, 2025)
This thesis explores the creative and collaborative dynamics within advertising production, focusing on the directorial style of Marius Talampas, an award-winning Filipino director known for viral commercials. Through interviews and analysis, the study investigates how Talampas balances his artistic vision with the collaborative contributions of his production team and the demands of agencies and clients. The research delves into Talampas' strategies for fostering a collaborative environment, his approach to creative control, and how he communicates his vision to his team. It examines the interplay between the director's initial concept and the input of production staff, highlighting instances where team members' ideas significantly improved the final product. The study also addresses the challenges of balancing artistic integrity with the commercial objectives of advertising. Ultimately, this thesis aims to provide insights into the creative production techniques employed in the advertising industry, offering valuable information for practitioners and scholars. By documenting and analyzing Talampas' collaborative processes, the research contributes to a deeper understanding of the factors that contribute to the success of advertising campaigns in the Philippines and beyond.
Thesis
Keywords: Talampas, Marius -- Motion picture producers and directors; Motion pictures -- Philippines -- Production and direction; Motion pictures -- Philippines -- History and criticism; Motion picture producers and directors -- Philippines